Carbon cycling hysteresis in permeable carbonate sands over a diel cycle: Implications for ocean acidification. (25th November 2012) - Cyronak, Tyler; Santos, Isaac R.; McMahon, Ashly; Eyre, Bradley D.
Abstract : Dissolved inorganic carbon, dissolved oxygen, H +, and alkalinity fluxes from permeable carbonate sediments at Heron Island (Great Barrier Reef) were measured over one diel cycle using benthic chambers designed to induce advective pore‐water exchange. A complex hysteretic pattern between carbonate precipitation and dissolution in sands and the aragonite saturation state (ΩAr ) of the overlying chamber water was observed throughout the incubations. During the day, precipitation followed a hysteretic pattern based on the incidence of photosynthetically active radiation with lower precipitation rates in the morning than in the afternoon. The observed diel hysteresis seems to reflect a complex interaction between photosynthesis and respiration rather than ΩAr of the overlying water as the main driver of carbonate precipitation and dissolution within these permeable sediments. Changes in flux rates over a diel cycle demonstrate the importance of taking into account the short‐term variability of benthic metabolism when calculating net daily flux rates. Based on one diel cycle, the sediments were a net daily source of alkalinity to the water column (5.13 to 8.84 mmol m −2 d −1, depending on advection rates), and advection had a net stimulatory effect on carbonate dissolution. The enhanced alkalinity release associated with benthic metabolism and pore‐water advection may partially buffer shallow coral reef ecosystems against ocean acidification on a local scale.